True metabolizable energy, standardized amino acid digestibility, and digestibility of phosphorus in soybean expellers produced from conventional or high-oil varieties of soybeans fed to chickens - M. Cristobal; P.L. Utterback; H.H. Stein; C.M. Parsons (Poultry Science, 2025)
The objective was to test the hypothesis that nitrogen-corrected true metabolizable energy (TMEn), standardized amino acid (AA) digestibility, and apparent ileal P digestibility are not different in soybean expellers produced from high-oil soybeans (SBE-HO) compared with expellers produced from conventional soybeans (SBE-CV). The two soybean expellers contained approximately 46.3 % crude protein (DM basis). In Experiments 1 and 2, 2 precision-fed rooster assays were conducted to determine TMEn and standardized AA digestibility in SBE-CV and SBE-HO using conventional and cecectomized roosters, respectively. For each experiment, 6 replicate White Leghorn roosters per treatment were fasted for 26 h prior to crop intubation with 25 g of sample and excreta were collected for 48 h post-feeding. Data were analyzed as a one-way ANOVA for a completely randomized design. The TMEn of SBE-HO (3.261 kcal/g DM) was greater than SBE-CV (3.162 kcal/g DM). Standardized digestibility of most AA was approximately 90 %, and there were no differences between the two soybean expellers, but SBE-HO had greater (P < 0.05) concentration of some digestible AA compared with SBE-CV. In Experiment 3, an ad-libitum-fed broiler chicken assay was conducted to determine apparent ileal digestibility of P in SBE-HO and SBE-CV. Eighty commercial Ross 308 male chicks were fed a standard corn-SBM diet from 0 to 16 d of age, and experimental diets from d 17 to 21. The 2 experimental diets had a total Ca:total P ratio of 1.4:1 and TiO2 was used as a digesta marker. There were 5 chicks per pen and 8 replicate pens per treatment and the pen was the experimental unit. On d 21, chicks were euthanized and ileal digesta were collected. Data were analyzed as in Experiments 1 and 2. Apparent ileal P digestibility for SBE-CV (46.8 %) was not different compared with SBE-HO (40.6 %). Overall, data indicated that SBE-HO had greater TMEn, similar digestibility of AA and P, but greater digestible concentrations of some AA compared with SBE-CV for broiler chickens.